PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA HOTEL MARIAT SORONG, KOTA SORONG - Yerrynaldo Loppies (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
The developed tourism sector results higher and higher competition level among companies in Indonesia, especially service companies. The service companies compete attempt for strengthening marketing strategies. The companies feel need for maintaining the consumers in order not to move to other companies. Not except for the companies in service fields such as hotels that are more and more competitive and demand for using owned resources as well as possible. Hotel industry progress can be followed about the development through indicator levels of hotel stay rooms/accommodation, sold/used room totals, how long average guests stay and also development of other hotel or accommodation totals. Hotel classification stated by Tourism General Directorate, i.e.: Star hotels and other accommodations. The improvement of various hotel facilities and services really enforce competition among hotel managers in the efforts of enchanting consumers and maintaining the consumers. Mariat Hotel Sorong is a hotel that blends business and resort concepts and continues attempt so that it still stays towering and supports Indonesian Republic government programs both in tourism field and improving people welfare field.The problem in this research is: Is there service quality influence that consists of tangible,reliability, responsiveness, assurance and empathy toward consumers loyalty of Mariat Hotel Sorong?The used data in this research are primary data gained by distributing questionnaires to the consumers who stay at Mariat Hotel Sorong by using double linear regression analysis.Keywords: service quality, consumers loyalty